A longitudinal study of the distance that young people walk to school. (January 2015) - Chillón, P.; Panter, J.; Corder, K.; Jones, A.P.; Van Sluijs, E.M.F.
Abstract: Walking or cycling to school has been associated with important health benefits. Distance between home and school is the main correlate of active commuting to school, but how far children walk to school and how this changes as children age is unknown. Mode of commuting and objectively-assessed distance to school were measured at 3 time points: aged 9/10 years, 10/11 years and 13/14 years. Data were analysed using ROC-curve analyses. With age, children walked further to school; the threshold distance that best discriminated walkers from passive commuters was 1421 m in 10-year-olds, 1627 m in 11-year-olds and 3046 m in 14-year-olds. Future interventions should consider the distance that young people actually walk. Highlights: The distance walked to school changes when children age. The threshold distance that best discriminates walkers and passive commuters is 1.4 km for 10 years children and 3 km for 14 years adolescents. These threshold distances will help inform policy, practice and future intervention efforts.